The Association of Cell Division Regulated by DicC With the Formation of Viable but Non-culturable Escherichia coli O157:H7 - Pan, Hanxu; Dong, Kai; Rao, Lei; Zhao, Liang; Wang, Yongtao; Liao, Xiaojun (Frontiers in Microbiology, 2019)
The viable but nonculturable (VBNC) state, in which bacteria fail to grow on routine culture media but are actually alive, has been widely recognized as a strategy adopted by bacteria to cope with stressful environments. However, little is known regarding the molecular mechanism of VBNC formation. Here, we aimed to elucidate the specific roles of cell division regulatory proteins and the cell growth rate during VBNC Escherichia coli O157:H7 formation. We have previously found that expression of dicC is reduced by 20.08-fold in VBNC E. coli O157:H7 compared to non-VBNC cells. Little is known about DicC except that it, along with DicA, appears to act as a regulator of cell division by regulating expression of the cell division inhibitor DicB. First, our results showed that the VBNC cell number increased in the ΔdicC mutant as well as the DicA-overexpressing strain but decreased in the DicC-overexpressing strain induced by high-pressure carbon dioxide (HPCD), acid and H2O2. Furthermore, the growth rates of both the DicA-overexpressing strain and the ΔdicC mutant were higher than that of the control strain, while DicC-overexpressing strain grew significantly more slowly than the vector strain. The level of the dicB gene, regulated by dicA and dicC and inhibiting cell division, was increased in the DicC-overexpressing strain and decreased in the ΔdicC mutant and DicA-overexpressing strain, which was consistent with the growth phenotypes. In addition, the dwarfing cell morphology of the ΔdicC mutant and DicA-overexpressing strain were observed by SEM and TEM. Taken together, our study demonstrates that DicC negatively regulates the formation of the VBNC state, and DicA enhances the ability of cells to enter the VBNC state. Besides, the cell growth rate and dwarfing cell morphology may be correlated with the formation of the VBNC state.